Students' Capabilities In Determining The Theme Of Bugis Folklore Texts With Intrinsic Elements Approach - Nurkamila Suriadi S; Firman Saleh; Sam Hermansyah; Rudy Yusuf; Burhan Kadir (La Ogi : English Language Journal, 2022)
This study aims to describe the ability to determine the theme of Bugis folklore. Based on the table data, it can be concluded that the highest score obtained by students on the ability to understand the theme of intrinsic elements in the story text La Maddukkelleng is 4 and gets a score of 100 while the lowest score obtained by students is 2 so that they get a value of 50. The research design used in this research is a descriptive quantitative research design. The population of this research is the entire class VIII SMP, totaling 81 students and divided into four classes. Based on the results of this study, it was found that the Ability to Understand Intrinsic Elements in Bugis folklore texts with seven assessment indicators found the level of ability in the theme aspect was categorized as capable as much as 75% who got a score of 75-100.